2017
DOI: 10.4103/2249-4863.220031
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive cross-sectional study on menstrual hygiene and perceived reproductive morbidity among adolescent girls in a union territory, India

Abstract: Introduction:Menstruation is a milestone event in a girl's life and the beginning of reproductive life. Lack of knowledge and poor sanitary practices during menstruation has been associated with serious ill-health ranging from genital tract infections, urinary tract infections, and bad odor.Aim:This study aims to explore the knowledge, attitude, and practices about menstrual hygiene and perceived reproductive morbidity among adolescent school girls in Puducherry.Materials and Methods:A school based cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 11 publications
6
18
0
Order By: Relevance
“…Several participants described information about menstruation being transferred inter-generationally through their mother, grandmother, or other family members. Other research has yielded similar findings, which suggest that insufficient knowledge about puberty, reproductive health, and menstruation is transferred inter-generationally, leaving adolescent girls poorly informed and ill-equipped to cope with menstruation (Chandra-Mouli & Patel, 2017;Mathiyalagen et al, 2017;Narayan et al, 2001).…”
Section: Discussionmentioning
confidence: 63%
“…Several participants described information about menstruation being transferred inter-generationally through their mother, grandmother, or other family members. Other research has yielded similar findings, which suggest that insufficient knowledge about puberty, reproductive health, and menstruation is transferred inter-generationally, leaving adolescent girls poorly informed and ill-equipped to cope with menstruation (Chandra-Mouli & Patel, 2017;Mathiyalagen et al, 2017;Narayan et al, 2001).…”
Section: Discussionmentioning
confidence: 63%
“…Therefore, it is logical to assume that MHM practices may influence the risk of vaginal infections. Another recent cross-sectional study in India, showed an association between lower frequency of genitalia washing associated with higher self-reported symptoms of itching and pustules in the genitalia [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…[1516] The duration of menstrual flow in our study was 4–6 days for 78% girls, whereas in a study by Mathiyalagen et al . 76.9%[17] girls had bleeding for 3–5 days and in a study by Kanotra et al . the duration of menstrual flow was within 5 days in 96.3% of girls and 3.7% had prolonged menses (>5 days).…”
Section: Discussionmentioning
confidence: 99%